COVID-19 and seasonal influenza: a comparative analysis in patients with hematological malignancies. Issue 3 (23rd February 2022) - Modemann, Franziska; Niederwieser, Christian; Weisel, Katja; Bokemeyer, Carsten; Fiedler, Walter; Ghandili, Susanne
Abstract: The severity and mortality of COVID-19 and seasonal influenza were recently compared in the general population but not in patients with hematological malignancies. We analyzed the clinical courses of 79 patients with hematological malignancies and diagnosis of either SARS-CoV-2 ( n = 29) or influenza A or B infections ( n = 50) who were admitted or were already under treatment in the Department of Oncology, Hematology and Stem cell Transplantation at the University Medical Center Hamburg-Eppendorf, Germany, between 1 January 2012 and 31 January 2021. For COVID-19, we observed significantly higher rates of acute respiratory distress syndrome with 48% (14/29) compared to 14% (7/50) in the influenza group ( p = 0.001) as well as a significantly higher virus-associated 90-day mortality (41% vs. 12%, p = 0.005). Based on our results, we conclude that infections with SARS-CoV-2 are more severe than influenza A or B in patients with hematological malignancies.